2022
DOI: 10.1002/cld.1169
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nonalcoholic Fatty Liver Disease on the Outcomes of Coronavirus Disease 2019 Infection

Abstract: Content available: Audio Recording

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…However, no difference in mortality was observed in comparison to non-NAFLD patients[ 61 ]. Similar findings have also been reported in other studies[ 60 , 62 , 63 ]. However, a single-center study from India reported a nonsignificant difference in hospital stay and mortality in COVID-19 patients with or without NAFLD[ 64 ].…”
Section: Chronic Liver Diseasesupporting
confidence: 93%
See 1 more Smart Citation
“…However, no difference in mortality was observed in comparison to non-NAFLD patients[ 61 ]. Similar findings have also been reported in other studies[ 60 , 62 , 63 ]. However, a single-center study from India reported a nonsignificant difference in hospital stay and mortality in COVID-19 patients with or without NAFLD[ 64 ].…”
Section: Chronic Liver Diseasesupporting
confidence: 93%
“…The range may be an overestimate, as most of the studies were concentrated on hospitalized patients[ 59 ]. NAFLD (recently renamed metabolic dysfunction-associated fatty liver disease) is associated with factors like diabetes and obesity, which are known to aggravate COVID-19 severity[ 60 ]. An electronic health records-based study reported that CLD patients have an increased risk of acquiring COVID-19 with the highest odds in patients with NAFLD (adjusted OR: 13.11), nonalcoholic cirrhosis (adjusted OR: 11.5) and chronic hepatitis C (adjusted OR: 8.7)[ 41 ].…”
Section: Chronic Liver Diseasementioning
confidence: 99%
“…COVID-19 enters the cholangiocytes through ACE2-R and causes direct damage with liver enzyme alteration, including albumin, GGT, ALT, and AST [ 95 , 96 , 97 ]. Moreover, the cytokine storm activated in COVID-19 affects the liver directly.…”
Section: Covid-19 and Nafld (Non-alcoholic Fatty Liver Disease)mentioning
confidence: 99%
“…TNF- α , a pro-inflammatory protein, is produced by adipose tissue and liver macrophages and modifies the immune response in patients with NAFLD. This process has consequences for M1 macrophages, which are suppressed, while M2 macrophages have an intense activation [ 95 , 96 , 97 ]. Taking this statement into account, it is necessary to identify a targeted treatment to reduce FLI [ 95 , 96 , 97 ].…”
Section: Covid-19 and Nafld (Non-alcoholic Fatty Liver Disease)mentioning
confidence: 99%
“…No se ha demostrado claramente el mismo papel en los pacientes con hígado graso metabólico (en los que predominan factores de riesgo como obesidad y diabetes), hepatitis viral, hepatitis autoinmune o enfermedades colestásicas. Las terapias antivirales pueden iniciarse y continuarse teniendo en cuenta el riesgo de reactivación con medicamentos inmunosupresores (17,18,19) .…”
unclassified